A Diagnostic Dilemma: Waldenström's Macroglobulinemia/Plasma Cell Leukemia. (9th September 2012) - Sethi, Bhawna; Butola, K. S.; Kumar, Yogesh
Abstract : Waldenström's macroglobulinemia is a B-cell neoplasm characterized by infiltration of the bone marrow by a lymphoplasmacytic infiltrate and an IgM monoclonal gammopathy. It is an uncommon disease with overall incidence of approximately 3 per million persons per year, accounting for approximately 1% to 2% of all hematologic cancers. It has only one-sixth the estimated prevalence of plasma cell myeloma. Disease symptoms can be due to infiltration of bone marrow and other tissue sites by malignant lymphoplasmacytic cells or due to the effects of elevated serum IgM levels. However, patients may present with constitutional symptoms only or may be asymptomatic. In our case, patient presented with chief complaints of fatigability and dyspnoea and was misdiagnosed as plasma cell leukemia on peripheral blood film and bone marrow morphology, but turned out to be a case of Waldenström's macroglobulinemia on cytoflorometry. The patient was referred for chemotherapy but expired on 10th day of admission. The suspected cause of death was cardiorespiratory failure.